Mapeamento das classes de uso do solo urbano no setor norte do bairro Camobi -Santa Maria RS:1966-1992 - Becker, Elsbeth Léia Spode; Zibordi, Antonio Francisco Guerreiro (Geografia Ensino & Pesquisa, 2016)
Mapeamento das classes de uso do solo urbano no setor norte do bairro Camobi -Santa Maria RS:1966-1992